PENGARUH PENGGUNAAN MEDIA MANIK-MANIK TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK AL-IZHAR SCHOOL KECAMATAN TAMPAN KOTA PEKANBARU - Imelda Adelina Siagian; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the research which is conducted at children age 5-6 year at Al-Izhar Kindergarten is the low of children’s skill to recognize number concept. The research aims to prove that there is an effect of beads media for the skill in understanding the numeric concept. This research used quantitative research by using experiment and one group pretest-posttest design. The subjects of the research are 16 childrens. The data collecting method used are observation and documentation. The data analysis used is parametric statistics test, t-test related by using SPSS Windows ver 18.0. Based on the result of the data analysis about the ability in recognizing the concept of the numbers in the first observation (pre-test) and the observation conducted after the treatment (post-test) by used beads media the average score of the pre test is 9.6875 and the average score of post-test is 15.125. The conclusion of research shows that use beads nedia affect the age 5-6 years group children’s cognitive skill in recognizing the number concept at AL-Izhar kindergarten, it is proven that the beads media can help the children in training their cognitive skill in recognizing the number concept. The results of this study have percentages obtained pretest pretest 48,44 % and posttest 72,63%, then the effect of beads media for the cognitive skill in understanding the numeric concept is 72,63% - 48,44 % = 24,19%. The effect of use beads media to skill in recognizing the number concept of 5-6 years old children at al-izhar kindergarten tampan subdistrict pekanbaru is 24,19%.Key Words : beads media, skill in recognizing the number concept